TEACHERS AND PARENTS AWARENESS – A KEY FACTOR TO SUCCESS OF INCLUSIVE EDUCATION - Elisabeta Kafia (European Scientific Journal, ESJ, 2014)
In developing countries, as Albania is, the process of creating an inclusive education system is more difficult. Factors such as lack of available funding, administrative and policy level support, and properly trained personnel pose significant challenges that slow down the progress. Key factors influencing the success of inclusive education are, among others, education of student teachers and level of awareness among teachers and parents.